Resolutions of the All-Russian Central Executive Committee as a Source on the History of Religious Policy of the RSFSR in the Early 1930s - Drobotushenko, Evgeny; Andreeva, Svetlana; Karasev, Sergey; Lantsova, Yulia; Filimonov, Andrey (International Journal of Psychosocial Rehabilitation, 2020)
. The article analyzes some Decrees of the All-Russian Central Executive Committee of the regulating issues related to religious policy. The author notes that there are no serious special scientific publications containing a comprehensive analysis of a significant number of Decrees of All-Russian Central Executive Committee (All-Russian Central Executive Committee) up to this day. Based on this, the basis of the study were archival sources, namely documents of State Archive of Russian Federation. Decrees regulated ultimately various issues: management, protection of monuments, etc.